PICTURE SERIES: A STRATEGY TO ASSIST NURSING STUDENTS TO SPEAK ENGLISH - Muflihah, Tatik (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2018)
Speaking is an important skill among other. It can be used to measure the language learner’s ability. However, many language learners are reluctant to speak in English class. One of the reasons is the students do not know the way how to express their idea properly. Then teaching learning process should be designed to assist them to speak. This study will try at investigating the use of pictures to enhance students in speaking class. This is a class action research (CAR) which consists of two cycles. Each cycle involves some activities; plan, action, observation, and reflection. The subject of the study is the third semester of S1 nursing in academic year 2017/2018 that consist of 34. The instruments are in the form of observation and speaking test. The result of the study is expected to be beneficial for students in speaking class, especially to motivate students to speak, tomake easier the students in expressing the theme provided by the pictures, and to create interesting environment.